Hyperangulated blades or direct epiglottis lifting to optimize glottis visualization in difficult Macintosh videolaryngoscopy: a non-inferiority analysis of a prospective observational study - Wünsch, Viktor A.; Köhl, Vera; Breitfeld, Philipp; Bauer, Marcus; Sasu, Phillip B.; Siebert, Hannah K.; Dankert, Andre; Stark, Maria; Zöllner, Christian; Petzoldt, Martin (Frontiers in Medicine, 2023)
It is unknown if direct epiglottis lifting or conversion to hyperangulated videolaryngoscopes, or even direct epiglottis lifting with hyperangulated videolaryngoscopes may optimize glottis exposure in situations where Macintosh videolaryngoscopy turns out to be more difficult than expected. This study aims to determine if the percentage of glottic opening (POGO) improvement gathered by direct epiglottis lifting is non-inferior to the one gathered by conversion to hyperangulated videolaryngoscopy in these situations.Methods: One or more optimization techniques were applied in 129 difficult Macintosh videolaryngoscopy cases in this secondary analysis of a prospective observational study. Stored videos were reviewed by at least three independent observers who assessed the POGO and six glottis view grades. A linear mixed regression and a linear regression model were fitted. Estimated marginal means were used to analyze differences between optimization maneuvers.Results: 163 optimization maneuvers (77 direct epiglottis lifting, 57 hyperangulated videolaryngoscopy and 29 direct epiglottis lifting with a hyperangulated videolaryngoscope) were applied exclusively or sequentially. Vocal cords were not visible in 91.5% of the cases with Macintosh videolaryngoscopy, 24.7% with direct epiglottis lifting, 36.8% with hyperangulated videolaryngoscopy and 0% with direct lifting with a hyperangulated videolaryngoscope. Conversion to direct epiglottis lifting improved POGO (mean +49.7%; 95% confidence interval [CI] 41.4 to 58.0; P <.001) and glottis view (mean +2.2 grades; 95% CI 1.9 to 2.5; P <.001). Conversion to hyperangulated videolaryngoscopy improved POGO (mean +43.7%; 95% CI 34.1 to 53.3; P <.001) and glottis view (mean +1.9 grades; 95% CI 1.6 to 2.2; P <.001). The difference in POGO improvement between conversion to direct epiglottis lifting and conversion to hyperangulated videolaryngoscopy is: mean 6.0%; 95% CI -6.5% to 18.5%; hence non-inferiority was confirmed.When Macintosh videolaryngoscopy turned out to be difficult, glottis exposure with direct epiglottis lifting was non-inferior to the one gathered by conversion to hyperangulated videolaryngoscopy. A combination of both maneuvers yield the best result.The study was registered with ClinicalTrials.gov (NCT03950934).